In perpetual motion : travel behavior research opportunities and application challenges - Mahmassani, Hani S. (Pergamon, 2002)
Travel behaviour interacts in a deep way with how we work and play. Social, intellectual, economic and technological forces continually influence the spatial and temporal activity patterns of individuals and businesses. Developments in the production, dissemination, and consumption of information have important implications for how we use our time, and how we pursue the various work, sustenance and leisure activities of our daily existence. This book provides an authoritative assessment of the state-of-the-art in travel behaviour research and applications, and identifies the principal emerging.